A Literature Study on Collaborative Art Learning in Tasikmalaya Based on Paulo Freire's Pedagogy of the Oppressed - Husen, Wan Ridwan; Nugraha, M. Fahmi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This study examines collaborative dialogical learning in art education based on Paulo Freire's critical pedagogy. It aims to explore how the concept of collaboration can be integrated into school-based art learning by utilizing the cultural assets of Tasikmalaya as a contextual framework. This research employs a literature study method by analyzing primary sources, particularly Freire's Pedagogy of the Oppressed, along with secondary literature from academic journals related to critical pedagogy and art education. The analysis focuses on identifying key principles of dialogical learning and their relevance to collaborative practices in art education. The findings indicate that Freire's concept of dialogical collaboration can be applied as a problem-posing learning approach, where teachers and students engage as active participants in critically examining social and cultural realities. This model emphasizes peer-based collaboration, dialogue, and the development of critical consciousness. Furthermore, integrating local cultural practices in Tasikmalaya provides a meaningful context for fostering student engagement and cultural awareness. This study suggests that art education has the potential to function not only as a medium for developing aesthetic skills but also as a transformative practice that promotes critical thinking and empowers students to actively interpret and reshape their social environment.